Revitalizing Character Values in the Era of Disruption through the Strategic Role of Teachers as Student Personality Formers.: Revitalisasi Nilai-Nilai Karakter di Era Disrupsi melalui Peran Strategis Guru sebagai Pembentuk Kepribadian Siswa. - Wawan Akbar; Aida Farida; Sanra Halinade Damanik; Hasratuddin Hasratuddin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The era of disruption—driven by technological advancement, globalization, and social transformation—has significantly impacted education. Specific Background: In this context, the erosion of core character values among students, such as responsibility, honesty, and social concern, has become a critical concern, exacerbated by the digital environment and a culture of instant gratification. Knowledge Gap: Despite ongoing educational reforms, limited empirical attention has been given to the adaptive role of teachers in preserving and revitalizing character education within contemporary challenges. Aims: This study aims to analyze the strategic roles played by teachers in fostering student character development amidst disruptive change. Results: Employing a qualitative method through literature review and targeted field observations in several high schools, findings highlight that teachers act as role models, facilitators of moral values, and cultivators of character-based school culture. Novelty: The study identifies the integration of character values in teaching, digital media, and extracurricular reinforcement—combined with collaboration among teachers, parents, and communities—as a comprehensive and adaptable strategy. Implications: These insights underscore the necessity for educators to commit to character education while evolving in tandem with societal and technological progress. Highlights: Teachers are key agents in shaping student character amid disruption. Integration of values into learning and extracurriculars is essential. Collaboration with parents and communities strengthens outcomes. Keywords: Character Education, Teacher Role, Digital Disruption, Moral Values, Educational Strategy